PENGARUH MODEL PEMBELAJARAN TGT BERBANTUAN WORDWALL TERHADAP PEMAHAMAN KONSEP IPAS KELAS IV SDN GUGUS VI KECAMATAN SUKASADA - I Made Ari Winangun; Ni Kadek Rina Widianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the differences in the ability to understand science concepts between groups of students who are taught using the Teams Games Tournament (TGT) learning model assisted by Wordwall media and groups of students who are taught using conventional learning models in grade IV elementary school students. The type of research used is a quasi-experimental design. The population in this study were all grade IV students of SDN Gugus VI Sukasada District in the 2025/2026 Academic Year. The research sample was determined using a random sampling technique, so that SD Negeri 1 Panji Anom was obtained as an experimental class with a total of 21 students and SD Negeri 2 Panji Anom as a control class with a total of 23 students. Data collection was carried out using a test method with an instrument in the form of 30 multiple-choice questions to measure the understanding of science concepts. The data obtained were then analyzed using descriptive statistics and inferential statistics, namely the polled variance t-test with the help of SPSS version 25. The results showed that the ability to understand science concepts of students in the experimental group was better than the control group. This can be seen from the average pre-test score of the experimental group of 65.00 which is higher than the control group of 60.00. In the post-test results, the average of the experimental group reached 91.67, while the control group was 72.13. In addition, the results of the independent sample t-test showed a significance value of 0.000 (α = 0.05), so that H₀ was rejected and H₁ was accepted. Thus, it can be concluded that the TGT learning model assisted by Wordwall media has a significant effect on the ability to understand the concept of science in grade IV students of SDN Gugus VI, Sukasada District.